Towards a hemispheric information infrastructure : some early harvests leading toward the FTAA (C/LAA WashingtonUS, 1996)
Defines the first results that have come forth from hemispheric telecommunications efforts since 1994. Looks at progress in the telecommunications sector in working to fulfill the mandate of the Summit of the Americas. Notes the progress in the area of private sector participation for both small and large economies. Focuses on progress in the use of telecommunications in social development for both small and large economies.
DC